The relationship between social support and demographic characteristics among Malaysian university students during the Covid-19 pandemic - Hussain, Mohd Rizal; Abdul Rahim, Nor Syazila; Abdul Aziz, Fatma Azwani; Umar, Rahmawati; Yap, Wing Fen; Hassan, Aminuddin; Md Shahril, Norshahilda; Mohd Fauzi, Muhammad Fathul Ariffin; Abdullah, Amini Amir (Macrothink Institute, 2021)
The COVID-19 pandemic is one of the fastest and most widespread epidemics affecting the world today, and its impacts are also experienced in Malaysia. The pandemic has a huge impact on the social, economic, and educational livelihood of the community. Furthermore, the government’s implementation of the Movement Control Order (MCO) has resulted in most sectors not operating at full capacity, including higher education institutions. This situation has largely affected the field of education. Thus, this study was conducted to explore the relationship between social support and demographic characteristics among the Universiti Putra Malaysia (UPM) students during the COVID-19 pandemic. The study adopted the quantitative survey research design and involved 468 randomly sampled participants. Data were collected using a digital questionnaire developed using Google Form and distributed through social media applications. The Statistical Package for the Social Science (SPSS) software was used to analyze the data obtained. The study’s findings showed that there was no significant difference between social support and sociodemographic backgrounds. Apart from that, the study also found a significant correlation between the three elements of social support (family, peer, and other close individual). Therefore, continuous social support must be fully utilized in order to avoid the emergence of any issues that can have a negative impact on students, thereby affecting their academic achievement and progress.